On prime and semiprime near-rings with derivations - Nurcan Argaç (International Journal of Mathematics and Mathematical Sciences)
Let N be a semiprime right near-ring, A a subset of N such that 0∈A and AN⫅A, and d a derivation of N The purpose of this paper is to prove that if d acts as a homomorphism on A or as an anti-homomorphism on A, then d(A)={0}.